ECONOMIC ANALYSIS OF MINI COAL GASIFIER (GasMin) COMMERCIALIZATION FOR SMALL AND MEDIUM INDUSTRIES (SMIs) - Ijang Suherman (Indonesian Mining Journal, 2020)
The Research and Development Centre for Mineral and Coal Technology (tekMIRA) has conducted a research on the GasMin since 2011, and currently enters the commercialization stage with a partnership scheme (KSO). This technology is one solution to solve the problem regarding the availability of cheap, clean and sustainable energy as well as environmentally friendly which is specifically intended for SMIs. Economic analysis is one of the activities in the commercialization process. From the analysis results, it can be seen that the Net Present Value of IDR is 808,273,705, the Internal Rate of Return 28.68% per year and the Payback Period 3 years and 8 months. The three indicators show that the project is financially feasible, with a level of sensitivity to changes in production costs is up to a 5% increase, and a level of sensitivity to a decrease in selling prices is up to -4%. This economic analysis is very important for both tekMIRA as a technology provider to find out the value of technology, and its potential partners as input in making decisions as a partnership with tekMIRA.